Advances in Soft and Hard Computing - Pejaś, Jerzy; El Fray, Imed.; Hyla, Tomasz; Kacprzyk, Janusz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book presents a collection of carefully selected, peer-reviewed papers from the 21st International Multi-Conference on Advanced Computer Systems 2018 (ACS 2018), which was held in Międzyzdroje, Poland on September 24th-26th, 2018. The goal of the ACS 2018 was to bring artificial intelligence, software technologies, biometrics, IT security and distance learning researchers in contact with the ACS community, and to give ACS attendees the opportunity to exchange notes on the latest advances in these areas of interest. The primary focus of the book is on high-quality, original and unpublished research, case studies, and implementation experiences. All of the respective papers are of practical relevance to the construction, evaluation, application or operation of advanced systems. The topics addressed are divided into five major groups: artificial intelligence, software technologies, information technology security, multimedia systems, and information system design.
Fitting Dense and Sparse Reduced Data -- Survey of AI Methods for the Purpose of Geotechnical Proﬁle Creation -- Algorithm for Optimization of Multi-spindle Drilling Machine Based on Evolution Method -- Method with Horizontal Fuzzy Numbers for Solving Quadratic Fuzzy Equation -- Regression Technique for Electricity Load Modeling and Outlined Data Points Explanation -- Correct Solution of Fuzzy Linear System Based on Interval Theory -- Processing of Z+ Numbers Using the k Nearest Neighbors Method -- Fingerprint Feature Extraction with Artiﬁcial Neural Network and Image Processing Methods -- An Investment Strategy Using Temporary Changes in the Behavior of the Observed Group of Investors -- Measuring Gender Equality in Universities -- Transitive Closure based Schedule of Loop Nest Statement Instances -- Design of the BLINDS System for Processing and Analysis of Big Data - A Pre-processing Data Analysis module -- QoS and Energy Eﬃciency Improving in Virtualized Mobile NetworkEPC based on Load Balancing -- The Approach to Users Tasks Simpliﬁcation on Engineering Knowledge Portals -- Repository Model for Didactic Resources -- SLMA and Novel Software Technologies for Industry 4.0 -- Applications of Multilingual Thesauri for the Texts Indexing in the Field of Agriculture -- On Code Refactoring for Decision Making Component Combined with the Open-source Medical Information System -- Programmable RDS Radio Receiver on ATMEGA88 Microcontroller on the Basis of RDA5807M Chip as the Central Module in Internet of Things networks -- Business Process Modelling with Cognitive EPC Diagram -- Algorithmic Decomposition of Tasks with a Large Amount of Data -- Managing the Process of Servicing Hybrid Telecommunications Services. Quality Control and Interaction Procedure of Service Subsystems -- Validation of Safety-Like Properties for Entity-Based Access Control Policies -- Randomness Evaluation of PP-1 and PP-2 Block Ciphers Round Keys Generators -- New Results in Direct SAT-based Cryptanalysis of DES-like Ciphers -- Secure Generators of q-valued Pseudo-random Sequences on Arithmetic Polynomials -- A Hybrid Approach to Fault Detection in One Round of PP-1 Cipher -- Protection of Information from Imitation on the Basis of Crypt-code -- On a New Intangible Reward for Card-Linked Loyalty Programs -- KaoChow Protocol Timed Analysis -- Electronic Document Interoperability in Transactions Executions -- L-system Application to Procedural Generation of Room Shapes for 3D Dungeon Creation in Computer Games -- Hardware-Eﬃcient Algorithm for 3D Spatial Rotation -- Driver Drowsiness Estimation by Means of Face Depth Map Analysis -- Vehicle Passengers Detection for Onboard eCall-Compliant Devices -- An Algorithm for Computing the True Discrete Fractional Fourier Transform -- Region Based Approach for Binarization of Degraded Document Images -- Partial Face Images Classiﬁcation Using Geometrical Features -- A Method of Feature Vector Modiﬁcation in Keystroke Dynamics -- Do-It-Yourself Multi-material 3D Printer for Rapid Manufacturing of Complex Luminaries -- Multichannel Spatial Filters for Enhancing SSVEP Detection.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence